Pengaruh Terapi Dingin Kompres Es Terhadap Perubaha Intesitas Nyeri Pada Penderita Nyeri Punggung Bawah Di Desa Risa Wilayah Kerja Puskesmas Woha Tahun 2019 - Supriadin, Supriadin; Wahidah, Wahidah; Lestari, Ayu Wahyuni (Barongko: Jurnal Ilmu Kesehatan, 2024)
Background : Lower back pain is one of the musculoskeletal disorders that often occurs and causes a decrease in work productivity and disability . Low back pain is a major cause of disability that affects work and general well-being. One way to reduce lower back pain is by giving cold compresses to cold compresses. Cold compresses can provide changes to the skin, subcutaneous tissue, kular itramus and temperature in the joints. Method : The research design used in this study was the One Group Pre-Test-Post Test Design. The independent variable is cold compress ice therapy while the dependent variable is low back pain. Sampling was done based on inclusion criteria with a sample of 30 people. Analysis of data using the Wilcoxon Signed Rank Test. Results : After being given cold compress ice therapy, low back pain which was originally severe pain dropped to moderate pain. Conclusion : There is an effect of cold compress ice therapy on changes in low back pain in patients with low back pain in the risa village work area of ​​Woha Puskesmas.